2022
DOI: 10.3390/bs12050141
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Belgium during the First 15 Months of the COVID-19 Pandemic: A Longitudinal Study

Abstract: The COVID-19 pandemic and policy measures enacted to contain the spread of the coronavirus have had nationwide psychological effects. This study aimed to assess the impact of the first 15 months of the COVID-19 pandemic on the level of anxiety (GAD-7 scale) and depression (PHQ-9 scale) of the Belgian adult population. A longitudinal study was conducted from April 2020 to June 2021, with 1838 respondents participating in 6 online surveys. Linear mixed models were used to model the associations between the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 73 publications
(93 reference statements)
1
18
0
Order By: Relevance
“…However, although time trends were similar for all population subgroups, higher levels of both anxiety and depression were generally found in young people. 25 Conversely, a longitudinal study conducted among 988 adults in Argentina showed a gradual increase in anxiety and depression between August 2020 and April 2021. 26 Again, young adults had higher prevalence rates of symptoms than other age groups.…”
Section: Jama Network Open | Psychiatrymentioning
confidence: 98%
See 2 more Smart Citations
“…However, although time trends were similar for all population subgroups, higher levels of both anxiety and depression were generally found in young people. 25 Conversely, a longitudinal study conducted among 988 adults in Argentina showed a gradual increase in anxiety and depression between August 2020 and April 2021. 26 Again, young adults had higher prevalence rates of symptoms than other age groups.…”
Section: Jama Network Open | Psychiatrymentioning
confidence: 98%
“…After gender-and degree-standardization, prevalence rates were slightly lower ( respectively). The medians (IQRs) of the scores were 45 for the STAI Y-2 (anxiety), 8 (4-13) for the BDI-13 (depression), 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) for the PSS-10 (stress), and 22 (10-37) for the PCL-5 (PTSD).…”
Section: Mental Health Outcomes and Associated Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some data of the COVID-19 health surveys were presented in the Mental health dashboard, an online tool that brings together several sources of data on the mental health of the general population (46). Lastly, the data of the COVID-19 health surveys were used in multiple scienti c publications (7,9,11,47,48).…”
Section: 2 Publication Of the Resultsmentioning
confidence: 99%
“…On the one hand, they should convey correct knowledge of epidemic prevention and guide the public to protect themselves from COVID-19 [ 9 ]; on the other hand, they should disseminate the true situation of the epidemic to the public. Therefore, the objectivity and impartiality of the news media are particularly important [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%